Long-term fertilization and liming increase soil fertility but reduce carbon stratification and stocks of paddy rice soils - Amoakwah, Emmanuel; Kim, Seong-Heon; Jeon, Sangho; Shim, Jae-Hong; Lee, Yun-Hae; Kwon, Soon-Ik; Park, Seon-Jin (Frontiers in Soil Science, 2024)
Introduction There is lack of information on the impact of acidity correctives (lime and silicate) and nitrogen (N), phosphorus (P), and potassium (K) fertilizers on the fertility, carbon stocks, carbon stratification, and carbon sequestration potential of paddy soils. To fill this knowledge gap and contribute to knowledge on how the treatments impact the soil ecosystem functions and services, a long-term field experiment was established in 1954 with four treatments and five replicates arranged in a randomized complete block design. Methods Four treatments with five replicates per treatment were laid out in a randomized complete block design. The treatments included control/untreated (CT), only NPK, silicate-fortified NPK (NPKSi), and lime-fortified NPK (NPKLi). The treatments were applied to paddy soils classified as Fluvaquentic Eutrudepts. Results and discussion Application of the treatments led to significant increases in soil pH by 0.9, 1.12, and 1.5 pH units in the NPK, NPKLi, and NPKSi-treated soils in 2021, respectively, compared to the initial soil pH. The increase in pH subsequently led to significant reductions in C stratification and C stocks, with reduced rates of C sequestration observed to be more pronounced in the soils treated with lime and silicate-fortified NPK fertilizers (NKPSi and NPKLi). Both NPKSi and NPKLi moderately increased soil fertility. The highest increase in soil fertility was observed in the NPKSi treatment, with an annual growth rate of 0.0160 and a relative change ratio of 128.2% relative to the initial soil fertility index recorded in 1970. A Pearson correlation analysis revealed that soil pH, exchangeable calcium, and available silicate were the soil properties that significantly contributed to the increase in the soil fertility of the treated soils in the rice paddy agroecosystem. Significance Conclusively, the inclusion of silicate in long-term fertilization is an effective strategy to mitigate soil acidity and increase soil fertility.